Operation Bangladesh - Gautam, P. K. (Pradeep Kumar), 1951- (New Delhi : Manas Publications, 2007)
Articles on military campaigns initiated by India at the time of independence struggle in Bangladesh in 1971.
Includes bibliographical references and index.
Keywords: Bangladesh -- History -- Revolution, 1971 -- Campaigns; India -- Military relations -- Bangladesh; Bangladesh -- Military relations -- India